Multi-Agent-Based Simulation VIII International Workshop, MABS 2007, Honolulu, HI, USA, May 15, 2007, Revised and Invited Papers - Antunes, Luis; Paolucci, Mario; Norling, Emma (Lecture Notes in Artificial Intelligence, 2008)
This book constitutes the thoroughly refereed post-proceedings of the 8th International Workshop on Multi-Agent-Based Simulation, MABS 2007, held in Honolulu, HI, USA in May 2007 as an associated event of AAMAS 2007, the main international conference on autonomous agents and multi-agent systems. The 10 revised full papers presented were carefully reviewed and selected from 20 submissions.The papers are organized in topical sections on architectures; teams, learning, education; economy, trust and reputation.